Heavy flavour decay muon production at forward rapidity in proton-proton collisions at s=7 TeV - Abelev, B.; Adam, J.; Adamovã, D.; Adare, A.M.; Aggarwal, M.M.; Aglieri Rinella, G.; Agócs, A.G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad, N.; Ahmad Masoodi, A.; et al. (Elsevier, 2012)
The production of muons from heavy flavour decays is measured at forward rapidity in proton–proton collisions at √s = 7 TeV collected with the ALICE experiment at the LHC. The analysis is carried out on a data sample corresponding to an integrated luminosity L_int = 16.5 nb⁻¹. The transverse momentum and rapidity differential production cross sections of muons from heavy flavour decays are measured in the rapidity range 2.5 < y < 4, over the transverse momentum range 2 < p_t < 12 GeV/c. The results are compared to predictions based on perturbative QCD calculations.
Keywords: LHC; ALICE experiment; pp collisions; Single muons; Heavy flavour production; https://purl.org/pe-repo/ocde/ford#1.03.03